Green Synthesis of Biodiesel from Pliek U Oil using Oyster Shell–Derived Calcium Oxide Modified with PVA: Structural Characterization and Catalytic Performance - Fauzi, Masyithah; Syifa, Maulidhia; Syafika, Nurul; Bhernama, Bhayu Gita (Departemen Kimia, 2026)
The production of biodiesel from local resources is a strategic approach to support sustainable energy transition. This study aimed to synthesize and evaluate the performance of a heterogeneous catalyst derived from oyster shell-based calcium oxide (CaO) modified with polyvinyl alcohol (PVA) as a binder, for the transesterification of Pliek U oil into biodiesel. CaO was synthesized by calcining oyster shells at 800°C, followed by PVA modification to improve structural stability and catalytic activity. The catalyst was characterized using X-ray Diffraction (XRD) to observe crystal patterns, while the resulting biodiesel was analyzed by Gas Chromatography–Mass Spectrometry (GC-MS) and Fourier Transform Infrared Spectroscopy (FTIR) to identify methyl ester compounds. Physicochemical properties including density, viscosity, acid value, water content, and flash point were also evaluated. Transesterification was carried out at a methanol-to-oil molar ratio of 12:1, catalyst concentration of 2.29% w/w, reaction temperature of 60°C, and reaction time of 90 minutes. The results showed a biodiesel yield of 96%, with dominant components being methyl caprylate, methyl laurate, and methyl caprate. FTIR spectra confirmed the presence of characteristic functional groups of methyl esters. The biodiesel properties met the SNI 7182:2015.